2008
DOI: 10.1158/1078-0432.ccr-08-0754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Sphingosine Kinase-1 Expression in Human Astrocytomas Progression and Overall Patient Survival

Abstract: Purpose: To characterize the expression of sphingosine kinase-1 (SPHK1) in human astrocytomas and to investigate the association between SPHK1 expression and progression of astrocytomas. Experimental Design: The expression of SPHK1in normal human astrocytes, astrocytoma cell lines, and four pairs of matched astrocytoma tissues and their adjacent normal brain tissues were detected by quantitative reverse transcription-PCR and Western blot. In addition, SPHK1protein expression was examined in 243 cases of histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 52 publications
3
108
0
Order By: Relevance
“…SPHK1 overexpression results in oncogenic transformation of normal fibroblasts (15,16), whereas the absence of SPHK1 in mice protects against the development of colon adenomas (17,18). Up-regulation of SPHK1 has been observed in many different tumors, including breast (19,20), lung (21,22), colon (17,18), and glioma (23,24), and increased SPHK1 expression has been associated with a poor survival outcome in GBM (24) as well as breast (20) and lung cancer (22). This has made SPHK1 a target of interest in cancer for biotechnology and pharmaceutical companies.…”
mentioning
confidence: 99%
“…SPHK1 overexpression results in oncogenic transformation of normal fibroblasts (15,16), whereas the absence of SPHK1 in mice protects against the development of colon adenomas (17,18). Up-regulation of SPHK1 has been observed in many different tumors, including breast (19,20), lung (21,22), colon (17,18), and glioma (23,24), and increased SPHK1 expression has been associated with a poor survival outcome in GBM (24) as well as breast (20) and lung cancer (22). This has made SPHK1 a target of interest in cancer for biotechnology and pharmaceutical companies.…”
mentioning
confidence: 99%
“…S1P is generated by phosphorylation of sphingosine catalyzed by SPHK1. Previous studies have confirmed that overexpression of SPHK1 and increased S1P production promotes cell growth [29][30][31]. SPHK1 is frequently overexpressed in a varietly of solid tumors, suggesting a potential oncogenic function and an important role in human tumorigenesis.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, separating our patients by S1P/weight ratio demonstrated two distinct groups of patients, with low (<10, 3.80-8. 26) and high (>10, 10.13-18.75) S1P/weight ratios who had 2.015±0.81 kg vs -0.14±0.77 kg weight change respectively, p=0.049 (Fig. 1 B).…”
Section: Circulating S1p Levels Correlate With Weight Gainmentioning
confidence: 89%
“…SphK1 has been found to be a tumor-associated enzyme: high levels of SphK1 expression have been shown in various human tumor tissues such as brain, breast, colon, lung, ovary, stomach, uterus, kidney, rectum and small intestine [22,23]. High levels of SphK1 expression and activity is associated with a poor prognosis in breast cancer [24], glioblastoma multiforme [25], astrocytoma [26] and gastric cancer [27].…”
Section: Introductionmentioning
confidence: 99%